1999
DOI: 10.1046/j.1365-2036.1999.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ranitidine bismuth citrate plus clarithromycin with omeprazole plus clarithromycin for the eradication of Helicobacter pylori

Abstract: Background : Many dual and triple therapy treatment regimens have been proposed for the eradication of Helicobacter pylori. However, assessing the relative efficacy of these regimens is complicated by differences in study design, and few well‐controlled comparative studies have been reported. Methods : This multicentre, randomized, double‐blind study involved 530 duodenal ulcer patients, of whom 520 had confirmed H. pylori infection. Patients received 14 days b.d. dual therapy of either ranitidine bismuth citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Eleven of the studies were multicentre RCTs [15,21,25,29,31,32,34,39,41,44,45] . Duration of bismuth therapy ranged from 7 to 56 d, with a total daily dose of between 400 mg and 2100 mg. Nineteen studies used ranitidine bismuth citrate [15,17,20,22,24,[28][29][30][31][32]34,36,[39][40][41]43,45,46,48] , ten studies colloidal bismuth subcitrate [7,16,18,21,26,27,37,38,42,44] , two studies tripotassium dictrato bismuthate [23,35] , two studies bismuth subsalicylate [25,33] , one study bismuth subnitrate [19] , and one study both bismuth subnitrate and www.wjgnet.com…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven of the studies were multicentre RCTs [15,21,25,29,31,32,34,39,41,44,45] . Duration of bismuth therapy ranged from 7 to 56 d, with a total daily dose of between 400 mg and 2100 mg. Nineteen studies used ranitidine bismuth citrate [15,17,20,22,24,[28][29][30][31][32]34,36,[39][40][41]43,45,46,48] , ten studies colloidal bismuth subcitrate [7,16,18,21,26,27,37,38,42,44] , two studies tripotassium dictrato bismuthate [23,35] , two studies bismuth subsalicylate [25,33] , one study bismuth subnitrate [19] , and one study both bismuth subnitrate and www.wjgnet.com…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Ten of the studies reported the method of generation of the randomization schedule [15,18,20,26,30,32,37,39,47,48] , but only four the method of concealment of allocation [27,32,47,48] . Four of the studies recorded adverse events using a questionnaire [20,24,28,40] , but only two of these stated that the questionnaire was validated [24,28] .…”
Section: Trial Qualitymentioning
confidence: 99%
See 3 more Smart Citations